Under a watchful eye : self, power, and intimacy in Amazonia - Walker, Harry, 1977- (Ethnographic studies in subjectivity, 2012)
What does it mean to be accompanied? How can autonomy and a sense of self emerge through one's involvement with others? This book examines the formation of self among the Urarina, an Amazonian people of lowland Peru. Based on detailed ethnography, the analysis highlights the role of intimate but asymmetrical attachments and dependencies which begin in the womb, but can extend beyond human society to include a variety of animals, plants, spirits and material objects. It thereby raises fundamental questions about what it means to be alive, to be an experiencing subject, and to be human. From the.